Preparation of future teachers for innovative activities in pedagogical and technological educational environment - N. I. Naumkin; N. N. Shekshaeva; V. F. Kupryashkin; E. V. Zabrodina (Russian State Vocational Pedagogical University, 2022)
Introduction. Innovative activity, as a creative productive activity, has always been and remains the basis for ensuring the progress of society and innovative training is one of the priorities of educational institutions. These aspects become especially relevant in relation to the professional training of future technology teachers, who will have to prepare the younger generation for the innovative activity at the initial stage of their training and form a stable opinion among them about the need to acquire knowledge and skills required for innovative activity. To solve these problems, most researchers create an educational environment (EE) of the appropriate model (developing, innovative, ecological, etc.). However, they do not address the issues of preparing technology teachers for innovation and do not fully utilise all available educational resources, including digital ones. In this regard, there is a problem of creating a new innovative pedagogical and technological educational environment (IPTEE).Aim. The current research aimed to identify and substantiate the possibility of effective preparation of future technology teachers for innovative activities when teaching in an innovative pedagogical and technological educational environment.Methodology and research methods. The research methodology is based on the following conceptual provisions: 1) innovative activity has arisen together with the formation of human society and has always determined its development; 2) one of the main tasks of each university is the innovative training of students; 3) the training of innovative activity is understood as the formation of students' competence in innovative activity; 3) the training of innovative activity is most effectively carried out in conditions for the formation of an appropriate educational environment. To implement the aforementioned provisions, the updated authors' methodological system of research on the problem of innovative training of university students was used. Such methodological system provides the implementation of mixed, project, "inverted" and other methods of teaching innovation in the basis of integrated, convergent, environmental and other approaches to learning.Results and scientific novelty. The main result of the research is the formation of a new didactic category - an innovative pedagogical and technological educational environment. The environment includes conceptually-targeted, infrastructural, content-based, psychological-didactic, methodological-technological and relaxation-diagnostic components, its features are the following: 1) focus on innovative training of technology teachers as directly related to the material objects of the innovative economy of the country; 2) universality in the form of the possibility of using it to solve other educational tasks; 3) graphical visualisation of the environment model with an indication of the hierarchy and interrelation of components, its scale, combinatoricity and functional sufficiency; 4) compliance of the environment with all the requirements of regulatory documents on educational activities at the university; 5) possibility of full-scale implementation of modern approaches to learning (innovative, personalised, environmental, project, etc.); 6) possibility of constant monitoring and control of the implementation of the environment within its relaxation and diagnostic component; 7) use of modern educational technologies, including digital; 8) possibility of obtaining specialised knowledge and studying other disciplines within the framework of using network learning; 9) innovativeness of the environment, determined by the novelty of the approach to teaching the teachers innovation technology and its effectiveness.To teach innovation activity in this environment, a model of a methodological system for the formation of competence in innovation activity among future technology teachers has been created, combining conceptually-targeted, meaningful, instrumental-activity and reflexive-evaluative components. The scientific novelty of the proposed approaches lies in the fact that without violating the structure and content of the curriculum, innovative training of students is guaranteed.Practical significance. The methodological system of research and the concept of innovation activity are concretised, its structure is developed, effective methods of training of future technology teachers for innovation activity are substantiated, and the methodology for teaching innovation activity in an innovative pedagogical and technological educational environment is developed.